Efficacy of parathyroid autotransplantation in endoscopic total thyroidectomy with CLND - Cheng, Xiaozhou; Li, Yaping; Chen, Lijun (Frontiers in Endocrinology, 2023)
Purpose: To evaluate the safety and efficacy of autologous parathyroid transplantation in endoscopic total thyroidectomy with central lymph node dissection. Methods: Retrospective analysis of clinical data of 152 patients admitted to the Department of General Surgery of Gansu Provincial People's Hospital from June 2018 to December 2021 for endoscopic total thyroidectomy with central lymph node dissection. Results: The rate of transient hypoparathyroidism was higher in the transplant group than in the non-transplant group (38.75% vs. 23.61%), and the incidence of permanent hypoparathyroidism was lower than in the non-transplant group (0% vs. 2.78%) The difference was statistically significant (X2=5.438, p=0.044). In the comparison of PTH in the elbow fossa head vein of both arms of patients in the graft group, the grafted side was higher than the non-grafted side at 1 d and 3 d after surgery, but the difference was not statistically significant (P>0.05); the grafted side was significantly higher than the non-grafted side at 1 week, 1 month, 3 months and 6 months after surgery, and the difference was statistically significant (P<0.001). The mean number of lymph nodes cleared in the central region per case was (9.08±3.17) in the transplantation group, which was higher than (7.86±2.45) in the non-transplantation group, with a statistically significant difference (P<0.05). The mean number of metastatic lymph nodes cleared per case was (3.36±1.71) in the transplantation group, which was higher than that of (2.83±1.51) in the non-transplantation group, and the difference was statistically significant (P<0.05). Conclusions: Most autografted parathyroid glands are PTH-secreting, and immediate active autografting of parathyroid glands can help reduce the incidence of hypoparathyroidism after endoscopic total thyroidectomy with central lymph node dissection, which is an effective strategy to prevent permanent hypoparathyroidism and allows for more complete dissection of central lymph nodes to facilitate disease regression.